Histopathological evaluation of endometrial glycogen deficiency in primary and secondary infertile women in Bangladesh: a cross-sectional study - Yasmin, Rumana; Rahman, Farhana; Afroz, Sadia; Haque, Sonia Mahmuda; Islam, Sabrina; Faruque, Nafis (International Journal of Advances in Medicine, 2025)
Background: Infertility is a major public health issue, affecting a significant proportion of couples worldwide. Endometrial receptivity, influenced by glycogen content, plays a crucial role for successful implantation. This study aimed to evaluate the glycogen content and histomorphological patterns of the endometrium in infertile women in Bangladesh, focusing on differences between primary and secondary infertility. Methods: This cross-sectional observational study was conducted at BIRDEM General Hospital, Dhaka, from July 2019 to June 2021. A total of 110 endometrial samples from infertile women from both primary and secondary infertility were analyzed. Samples were collected during the secretory phase of the menstrual cycle and assessed by using Hematoxylin and Eosin (H&E) and Periodic Acid Schiff (PAS) staining. Glycogen content was graded on a scale from ‘0’ to ‘++++’ and analyzed across different types of infertility and histomorphological patterns. Results: The majority of participants were aged 26-30 years (43.64%), with primary infertility being more prevalent (63.64%) than secondary infertility (36.36%). Deficient glycogen content was observed in 71.43% of primary infertility cases, compared to 60.00% of secondary infertility cases. Normal glycogen levels were more frequent in the secretory phase, particularly the late secretory phase, with 36 cases showing ‘+++’ and 5 cases showing ‘++++’ grades. Variations in glycogen content were also noted across histomorphological patterns, with Luteal Phase Defect (LPD) cases displaying mixed glycogen levels. Conclusion: The study underscores the importance of adequate glycogen content in endometrial receptivity and its association with infertility. The findings suggest that histopathological evaluation of glycogen levels, particularly using PAS staining, can be an effective diagnostic tool for assessing endometrial health in infertile women. Addressing glycogen deficiencies may improve reproductive outcomes, and further research is needed to understand the underlying mechanisms contributing to variability in glycogen content.